2018
DOI: 10.5194/acp-2018-816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification and quantification of particulate tracers of exhaust and non-exhaust vehicle emissions

Abstract: <p><strong>Abstract.</strong> In order to identify and quantify key-species associated with non-exhaust emissions and exhaust vehicular emissions a large comprehensive dataset of particulate species has been obtained thanks to simultaneous near-road and urban background measurements coupled with detailed traffic counts and chassis dynamometer measurements of exhaust emissions of a few in-use vehicles well-represented in the French fleet. Elemental Carbon, brake-wear me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…The highest concentration of Al among these heavy metals suggested a predominant contribution from crustal sources such as fugitive dust to the fine aerosols in Suzhou (Ma et al, 2019 ; Xu et al, 2021 ). While the dominance of Mn and Pb could be attributed to coal combustion (Deng et al, 2014 ) and traffic emissions including exhaust and non-exhaust emissions (Charron et al, 2018 ). Other heavy metals were ranked as: Cr > Sb > As > Ni > Se > Cd > Hg > Tl.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest concentration of Al among these heavy metals suggested a predominant contribution from crustal sources such as fugitive dust to the fine aerosols in Suzhou (Ma et al, 2019 ; Xu et al, 2021 ). While the dominance of Mn and Pb could be attributed to coal combustion (Deng et al, 2014 ) and traffic emissions including exhaust and non-exhaust emissions (Charron et al, 2018 ). Other heavy metals were ranked as: Cr > Sb > As > Ni > Se > Cd > Hg > Tl.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was noteworthy that the concentration of Cr(VI) in Suzhou was 0.66 ng m −3 , which was lower than some cities of Northern China such as Beijing (2.5 ng m −3 ) (Fan et al, 2021 ), Baoding (8.3 ng m −3 ) (Liu et al, 2018 ), and some cities of Eastern China such as Shanghai (3.2 ng m −3 ) (Chen et al, 2008 ), and some cities of Southern China such as Xiamen (3.7 ng/m 3 ) (Wang et al, 2017 ), and some other Asian cities such as Siheung (2.43 ng m −3 ) (Lee et al, 2022 ), but more than twenty times higher than the China standards of 0.025 ng m −3 . Many studies showed that the sources of Cr included brake and engine wear (Charron et al, 2018 ), industrial metalworking activities (Dai et al, 2015 ), and the incineration of plastic materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the spherical iron particles are combustion processes of steelmaking containing chromium. The metal particles of iron may come from the emissions of diesel engines, chromium oxide may exist in the filler of brake linings and can also be burned from lubricating oil [18], tin-rich particles may come from the fuel combustion of port vessels [19], titanium balls may come from the pigment manufacturing process [20], and irregular titanium sheets may come from road dust and wear of tires and brakes [21]. Sulfur-rich particles are irregular in shape and volatile under the electron beams, usually forming a "foam-like" structure.…”
Section: Micro Topography Feature Analysismentioning
confidence: 99%
“…7. Most iron balls come from the combustion process of steelmaking [18], while titanium balls come from pigment manufacturing [20]. The proportion of iron balls in the samples during the Winter Olympic Games is higher than that after the Winter Paralympic Games, and the average amount of particulate matter per day is lower than that after the Winter Paralympic Games, which indicates that the control effect of steel making industry is better during the Winter Olympic Games, but the control effect of other pollution sources is better, resulting in a higher proportion; The proportion of titanium balls in the samples of the Winter Olympic Games is higher than that before and after the Winter Olympic Games, but the average amount of particulate matter per day is lower than that before and after the Winter Olympic Games.…”
Section: Research On the Traceability Of Atmospheric Particulate Mattermentioning
confidence: 99%